2014
DOI: 10.1017/s2078633614000484
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of different indigenous chicken ecotypes using highly polymorphic MHC-linked and non-MHC microsatellite markers

Abstract: The study investigated the genetic make-up of different ecotypes of indigenous chickens (ICs) in Kenya based on major histocompatibility complex (MHC)-linked and non-MHC microsatellite markers. Blood samples were collected from eight regions (48 birds per region) of Kenya: Kakamega (KK), Siaya (BN), West Pokot (WP), Turkana (TK), Bomet (BM), Narok (NR), Lamu (LM) and Taita-Taveta (TT) and genotyped using two MHC-linked and ten non-MHC markers. All MHC-linked and non-MHC markers were polymorphic with a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
32
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 27 publications
11
32
1
Order By: Relevance
“…This is not surprising since these areas border each other geographically. These findings corroborated the observations of a study conducted in Kenya where the Mantel test had uncovered a positive association between hereditary and geographic distances [57]. Our study also confirmed that geographic distances affected the population's genetic structure [57].…”
Section: Phylogenetic Relationship and Population Structuresupporting
confidence: 92%
“…This is not surprising since these areas border each other geographically. These findings corroborated the observations of a study conducted in Kenya where the Mantel test had uncovered a positive association between hereditary and geographic distances [57]. Our study also confirmed that geographic distances affected the population's genetic structure [57].…”
Section: Phylogenetic Relationship and Population Structuresupporting
confidence: 92%
“…Consequently, there is a high influx of genes in these regions This is not surprising since these areas border each other geographically. These findings corroborated the observations of a study conducted in Kenya where the Mantel test had uncovered a positive association between hereditary and geographic distances [43]. Our study also confirmed that geographic distances affected the population’s genetic structure [43].…”
Section: Discussionsupporting
confidence: 92%
“…These findings corroborated the observations of a study conducted in Kenya where the Mantel test had uncovered a positive association between hereditary and geographic distances [43]. Our study also confirmed that geographic distances affected the population’s genetic structure [43]. The portion of SW chicken populations that clustered with the exotic chicken (control) could be attributed to the fact that different crossing programmes between IC and improved chicken breeds have been introduced in that region to improve the genetic potential of IC in Rwanda [44].…”
Section: Discussionsupporting
confidence: 91%
“…1 European Nucleotide Archive (ENA) https://www.ebi.ac.uk/ena/data/view/PRJEB1683; 2 (Bosse et al., ) 3 (Yang et al., ) 4 (Derks et al., ) 5 (Ngeno, ) 6 (Ngeno et al., ) 7 (Derks et al., ), 8 (Derks, Megens et al. (submitted)).…”
Section: Methodsmentioning
confidence: 99%
“…Re‐sequence data from a total of 76 pigs were retrieved from the European Nucleotide Archive (ENA) accession code ERP001813. Re‐sequence data from eight African village chicken were obtained from (Ngeno, and described in Ngeno et al., ). Since Ngeno, is a PhD thesis, the relevant vcf files of the village chicken are deposited into https://www.animalgenome.org/repository/pub/WUR2018.0809/.…”
Section: Data Archiving Statementmentioning
confidence: 99%